Efektivitas Remedial Terhadap Hasil Belajar Peserta Didik Dalam Pembelajaran Pendidikan Agama Islam - Imam Wahyudi; Faiarudin Aulia Widadi; Muhammad Ilham Akbar (CV. ITTC INDONESIA, 2024)
This article discusses the effectiveness of remedial learning scores for students in learning PAI (Islamic Religious Education) at the Tahfidzul Quran Muhammadiyah Al Firdaus Islamic Boarding School. This research focuses on the remedial objectives and learning outcomes of students at the Tahfidzul Quran Muhammadiyah Al Firdaus Islamic Boarding School. This research uses a qualitative field method which requires researchers to use observation techniques by interviewing teachers or caregivers at the Pondok. The results of this research point to the aim of holding remedial training to help students who have not yet achieved completeness to achieve the school's vision and mission. For students who have not been able to achieve completeness, remediation needs to be carried out. After taking the treatment, students had a good response and experienced an increase in their learning scores.